Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

High Ca2+ Influx During Traumatic Brain Injury Leads to Caspase-1-Dependent Neuroinflammation and Cell Death - P. M. Abdul Muneer; Mathew Long; Adriano Andrea Conte; Vijayalakshmi Santhakumar; Bryan J. Pfister (Molecular Neurobiology, 2017)

Improvement in carbohydrate and phlorotannin extraction from Macrocystis pyrifera using carbohydrate active enzyme from marine Alternaria sp. as pretreatment - A. Leyton; R. Pezoa-Conte; P. Mäki-Arvela; J-P Mikkola; M. E Lienqueo (Journal of Applied Phycology, 2017)

Is there an association between prior anti-inflammatory drug exposure and occurrence of peritonsillar abscess (PTA)? A national multicenter prospective observational case–control study - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Peritonsillar abscess (PTA): clinical characteristics, microbiology, drug exposures and outcomes of a large multicenter cohort survey of 412 patients hospitalized in 13 French university hospitals - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Comparative analysis of nutritional compositions of transgenic RNAi-mediated virus-resistant bean (event EMB-PV051-1) with its non-transgenic counterpart - José L. V. Carvalho; Juliana de Oliveira Santos; Carmine Conte; Sidney Pacheco; Elsa O. P. L. Nogueira; Thiago L. P. O. Souza; Josias C. Faria; Francisco J. L. Aragão (Transgenic Research, 2015)

Depth-dependent photodegradation of marine dissolved organic matter - Stephen A. Timko; Anastasia Maydanov; Sandra L. Pittelli; Maureen H. Conte; William J. Cooper; Boris P. Koch; Philippe Schmitt-Kopplin; Michael Gonsior (Frontiers in Marine Science, 2015)

Correlation between cortical plasticity, motor learning and BDNF genotype in healthy subjects - P. Li Voti; A. Conte; A. Suppa; E. Iezzi; M. Bologna; M. S. Aniello; G. Defazio; J. C. Rothwell; Alfredo Berardelli (Experimental Brain Research, 2011)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Bactericidal effect of pefloxacin and fosfomycin againstPseudomonas aeruginosa in a rabbit endocarditis model with pharmacokinetics of pefloxacin in humans simulated in vivo - D. Bugnon; G. Potel; Y. Q. Xiong; J. Caillon; D. Navas; C. Gras; M. F. Kergueris; P. Le Conte; F. Jehl; D. Baron; H. Drugeon (European Journal of Clinical Microbiology & Infectious Diseases, 1997)